Palaeoentomology of the Kap København Formation, a Plio-Pleistocene sequence in Peary Land, North Greenland - Böcher, Jens (Meddelelser om Grønland. Geoscience, 1995)
The Kap København Formation in eastern Peary Land, latitude 82°30', is dated to the Plio-Pleistocene transition period, c. 2 million years B.P. The shallow water marine sediments contain abundant remains of terrestrial and limnic insects, in particular beetles (Coleoptera). The insect fauna is diverse, comprising 155 named species, of which 140 are beetles. The Coleoptera are dominated by ground beetles (Carabidae), rove beetles (Staphylinidae) and weevils (Curculionidae). Apart from three unknown and possibly extinct species, including Diacheila matthewsi n. sp. described herein, all the insect taxa are extant. Most are extralimital forms of the recent circumpolar subarctic/boreal fauna. However, a high number of fossils represent taxa which are today either nearctic or palaearctic, in some cases with modern occurrences in northeastern Asia or western North America. Many species are hygrophilic (20 %), aquatic (16 %) or riparian (18 %), thereby showing the existence of a great variety of freshwater wetland biotopes. Another large group (14 %) are either dependent on trees for food or are obligate forest dwellers and therefore indicate forest environments. Still other species suggest arctic/alpine living conditions (14 %), and a few are indicative of steppe environments. The fossil insect fauna thus strongly supports and elaborates previous palaeo botanical results showing that Peary Land at the beginning of the Quaternary epoch was covered by a rich and varied vegetation, in the lowlands with trees and probably small forests. The palaeo climate was boreal and humid, with a July mean temperature of at least 8-11°C, but considerably warmer (13-19°C) in lowland areas or during certain time periods. There are indications of a shift in climate from subarctic to more southern boreal conditions during the deposition of the upper member (B) of the Kap København Formation.